2020
DOI: 10.1021/acsapm.0c01011
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufactured Carbon Nanotube/Epoxy Nanocomposites for Heavy-Duty Applications

Abstract: A solid epoxy resin formulation containing 2.5 wt % carbon nanotubes is 3D printed into self-standing parts, which after thermal curing result in CNTs/epoxy nanocomposites with mechanical properties attractive for heavy-duty applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…64 Recent reports have demonstrated that, using CNT ink as fillers drastically improved the electrical and mechanical properties of polymers. 64,65 Even in past, BMC, a leading Swiss bicycle brand, for the first time introduced complete bicycle frame with CNT nanocomposite. 66 In the year 2011, a company named Nanocomp Technologies, developed a CNT-based composite known as Emshield for NASA's Juno spacecraft for protection against electrostatic discharge (ESD).…”
Section: Carbon Nanotube (Cnt)-based Additive Technologymentioning
confidence: 99%
“…64 Recent reports have demonstrated that, using CNT ink as fillers drastically improved the electrical and mechanical properties of polymers. 64,65 Even in past, BMC, a leading Swiss bicycle brand, for the first time introduced complete bicycle frame with CNT nanocomposite. 66 In the year 2011, a company named Nanocomp Technologies, developed a CNT-based composite known as Emshield for NASA's Juno spacecraft for protection against electrostatic discharge (ESD).…”
Section: Carbon Nanotube (Cnt)-based Additive Technologymentioning
confidence: 99%
“…Nanoparticles were prepared and mixed with the printing lament to produce a new one[6, [17][18][19]. Some research focuses on improving the overall mechanical properties of the 3D printed part by decreasing its anisotropy or increasing its isotropic behavior [20,21].They replaced the thermoplastic polymers that results in poor chemical and thermal properties by two-component epoxy resin [20],epoxy resin poses good chemical and physical properties and gives high-strength bonding, with light weight structures withstanding high static loads [22,23]. Filippova et al [21] impregnated ABS 3D printed samples in epoxy resin compound with different hardeners.…”
Section: Introductionmentioning
confidence: 99%
“…This results in improving the overall part stiffness and strength by up to 25% and 45% respectively. Moreover, Jiang et al [20] used epoxy as the main raw material in FDM technique to get the best use of its mechanical properties and print products can be used in harsh conditions. Tensile specimens were printed of a mixture of only epoxy and CNT giving a tensile strength of 55 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fluids with shear thinning behavior and yield stress (yield pseudoplastic fluid) are commonly used for DIW, which can be self-supporting at the stationary state and has decreased viscosity during pressurized extrusion. 23,24 Because the regular neat thermosetting materials do not meet such requirements, modifications of the feedstocks or printing methods, such as reinforcing filler addition, 19,21,22,25,26 extruding through twopart mixing head 20 to deposition through two-part mixing head or after deposition by thermal curing with the aid of the filler inclusion. However, the DIW of resins infilled by inorganic fillers has a few drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The nozzle can deposit the materials in three dimensions layer by layer on the platform. Therefore, fluids with shear thinning behavior and yield stress (yield pseudoplastic fluid) are commonly used for DIW, which can be self-supporting at the stationary state and has decreased viscosity during pressurized extrusion. , Because the regular neat thermosetting materials do not meet such requirements, modifications of the feedstocks or printing methods, such as reinforcing filler addition, ,,,, extruding through two-part mixing head are necessary to accommodate this extrusion-based method. Correspondingly, curing can be conducted prior to deposition through two-part mixing head or after deposition by thermal curing with the aid of the filler inclusion.…”
Section: Introductionmentioning
confidence: 99%